A guide to the automation body of knowledge - Trevathan, Vernon L., ....- (Research Triangle Park, NC : ISA, The Instrumentation, Systems, and Automation Society, 2006)
A Guide to the Automation Body of Knowledge, 2nd Edition, has been updated and additional topics added covering custom software, control equipment structure, and continuous emissions monitoring systems to better provide the reader with comprehensive information about all major topics in the broad field of automation. Edited by Vernon L. Trevathan with contributions from over thirty-five leading experts from all aspects of automation, this book defines the most important automation concepts and processes, while also describing the technical skills professionals require to implement them in today's industrial environment. Whether you are an engineer, manager, control systems integrator, student, or educator, you will turn to this book again and again as the ultimate source on what is encompassed by automation.
Includes bibliographical references and index.
Keywords: Automation -- Handbooks, manuals, etc